ANALISIS KELAYAKAN INVESTASI PEMBANGKIT LISTRIK TENAGA SURYA PADA ATAP GEDUNG RUMAH SAKIT UNIVERSITAS UDAYANA - Ketut Mira Ardianti; Dyana Arjana; Indra Partha; Maharta Pemayun (Program Studi Teknik Elektro UNUD, 2025)
The increasing global electricity demand, predominantly met by fossil fuels, necessitates renewable energy development. Indonesia, with its vast solar potential, still faces limited implementation of Solar Power Plants (PLTS). This study analyzes the investment feasibility of a rooftop PLTS at Udayana University Hospital (RSPTN Universitas Udayana), utilizing 2023 electricity consumption data and current component pricing. The research aims to determine the Cost of Energy (COE), conduct a comprehensive economic analysis using Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and Payback Period (PP), and propose a suitable PLTS management model. Findings indicate strong financial viability for this PLTS investment. Calculations reveal a Life Cycle Cost (LCC) of Rp3,190,730,607, a Capital Recovery Factor (CRF) of 0.0746, and an estimated annual energy production of 498,955 kWh. The calculated COE is Rp803.00. The investment yields a positive NPV of Rp3,818,228,293, a PI of 2.357 (>1), and a Payback Period (PP) of 6 years and 9 months, well within the system's operational lifespan. The positive IRR (10.59%) further supports its financial viability, positioning this rooftop PLTS project as a sound and sustainable investment for RSPTN Universitas Udayana.